2021
DOI: 10.1080/15622975.2021.1907722
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study detected novel susceptibility genes for social cognition impairment in people with schizophrenia

Abstract: Objectives: People with schizophrenia (SCZ) present serious and generalised deficits in social cognition (SC), which affect negatively patients' functioning and treatment outcomes. The genetic background of SC has been investigated in disorders other than SCZ providing weak and sparse results. Thus, our aim was to explore possible genetic correlates of SC dysfunctions in SCZ patients with a genome-wide study (GWAS) approach. Methods: We performed a GWAS meta-analysis of data coming from two cohorts made of 242… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Two studies investigated also genetic aspects in this population ( 121 , 122 ). In particular, one study investigated de novo copy number variations (CNVs) in the whole-genomic DNA obtained from 46 family trios of schizophrenia probands.…”
Section: Cross-sectional Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies investigated also genetic aspects in this population ( 121 , 122 ). In particular, one study investigated de novo copy number variations (CNVs) in the whole-genomic DNA obtained from 46 family trios of schizophrenia probands.…”
Section: Cross-sectional Studymentioning
confidence: 99%
“…The authors reported the presence of de novo CNVs in genes involved in brain and neural development, suggesting that these alterations could contribute to the genetic vulnerability to the disorder ( 122 ). The study by Gennarelli et al ( 121 ) aimed to explore the genetic basis of social cognition, using a genome-wide study approach. The authors found significant associations between the patients' ability in social inference and the TMEM7M4 gene.…”
Section: Cross-sectional Studymentioning
confidence: 99%
“…Most subjects with schizophrenia experience a broad range of cognitive deficits in different neurocognitive domains, such as working memory, attention/vigilance, verbal/visual learning, reasoning/problem solving and executive functioning [ 3 , 14 , 33 , 34 , 35 , 36 ]. In addition, subjects with schizophrenia often show impairments in social cognition, a cognitive domain defined as a range of abilities guiding the interpretation of other’s emotions or intentions, leading to informed conclusions and behaviours [ 1 , 2 , 4 , 16 , 25 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%